The influence of work life balance and work environment on turnover intention mediated by job stress in gen z employees in Pontianak City - Jepri, Labensius Sudanuro; Ginting, Sunardi (International Journal of Enterprise Modelling, 2025)
Competitive work environments often trigger work stress, which negatively impacts employee performance and increases turnover intention. This condition requires effective stress management strategies to maintain productivity and reduce turnover rates. This study aims to analyze the impact of work stress management strategies on employee performance and turnover intention in a competitive work environment. The method used is a quantitative approach with a survey of 200 employees from various industries who face high work pressure. Data were analyzed using multiple regression models to measure the effect of stress management strategy variables on performance and turnover intention. The results showed that the implementation of effective stress management strategies, such as employee welfare programs, time management, and communication skills training, significantly improved employee performance and decreased turnover intention. The implication of this study is the importance of companies to design and implement sustainable stress management programs as part of organizational policies to create a healthy and productive work environment.